Exploring values among three cultures from a global bioethics perspective. (1st January 2021) - Nortjé, Nico; Jones-Bonofiglio, Kristen; Sotomayor, Claudia R.
ABSTRACT: The United Nations Educational, Scientific and Cultural Organisation's (UNESCO) Declaration on Bioethics and Human Rights refers to the importance of cultural diversity and pluralism in ethical discourse and care of humanity. The aim of this meta-narrative review is to identify indigenous ethical values pertaining to the Ojibway (Canada), Xhosa (South Africa), and Mayan (Mexico and Central American) cultures from peer-reviewed sources and cultural review, and to ascertain if there are shared commonalities. Three main themes were identified, namely illness, healing, and health care choices. Illness was described with a more complex and dynamic picture than from the western view, as illness is not considered to be one dimensional. Healing needs to take place on various levels in order to restore a state of equilibrium between the different spheres. Health care choices were also considered from a multi-level perspective. In all three of the indigenous cultures explored, good decision-making is seen to have occurred when choices are informed by commitments to one's moral and ethical responsibilities towards the community, nature, and the spirit world.